"There's No Supports for People in Addiction, But There's No Supports for Everyone Else Around Them as Well": A Qualitative Study With Parents and Other Family Members Supporting Youth and Young Adults. (June 2022) - Khan, Faria; Lynn, Michaela; Porter, Kym; Kongnetiman, Linda; Haines-Saah, Rebecca
ABSTRACT: Objectives: Harms from opioid use and opioid-related overdose death have continued to rise in Western Canada, constituting a public health emergency. While the presence of family support is essential to improving health outcomes for people who use drugs, affected family members continue to face considerable challenges in accessing timely and appropriate supports and services, both for their loved ones, and for themselves when needed. The overarching aim of our qualitative project was to employ qualitative methodology to understand family experiences with healthcare and treatment services when supporting a young person seeking treatment for use of opioids and/or other substance use. Methods: To understand the family experience of providing support for a youth or young adult who has experienced harms from opioids and other co-occurring substance use interviews (n = 17) were carried out in Alberta, Manitoba, and Saskatchewan, with adult family members (mostly mothers; 12/17) of youth and young adults who had experienced harms due to opioids and other substance use, including overdose death. Qualitative interview data was analyzed using Reflexive Thematic Analysis to distill themes. Results: We identified the following key themes from our analysis: (1) The challenges and stigma encountered when seeking care for a loved one using substances, and (2) The lack of support to address family member mental health needs. In addition to access and system navigation challenges, persistent experiences of stigma and discrimination within the healthcare system and from healthcare providers were prominent for family members and loved ones. There was also a reported lack of support for family members themselves, and very little formal support to address their experiences of social isolation, emotional distress, and grief when a child or family member experiences harms from drug use or dies. Conclusions: Our qualitative study provides in depth insights from family members whose perspectives have been marginalized and excluded from the literature on youth and young adult substance use treatment. The insights shared by parents, siblings, and others speak to the need to provide family-based supports that include support for caregiver mental health. Therefore, we conclude by making recommendations for approaches to youth addiction treatment that are more "family-focused" and supportive of not only the young people using substances but also the loved ones who care for them. Abstract : Objectifs: Les méfaits associés à l'usage d'opioïdes et les décès par surdose d'opioïdes continuent d'augmenter dans l'Ouest du Canada et constituent une urgence de santé publique. Malgré l'importance du soutien familial dans l'amélioration des résultats de santé des personnes atteintes d'un trouble lié à la consommation de substances psychoactives, les membres de la famille touchés éprouvent toujours une très grande difficulté à accéder rapidement aux services et au soutien appropriés, tant pour eux-mêmes que pour leurs proches. Notre projet qualitatif visait principalement à employer une méthode qualitative pour comprendre ce que vivent les familles qui ont recours aux services de soins de santé et de traitement pour accompagner une jeune personne qui cherche à traiter son usage d'opioïdes ou d'autres substances psychoactives. Méthodologie: Pour comprendre l'expérience d'une famille qui soutient un jeune ou un jeune adulte qui a subi des méfaits causés par l'usage d'opioïdes et d'autres substances psychoactives concomitantes, des entrevues (n = 17) ont été menées en Alberta, au Manitoba et en Saskatchewan, avec des membres adultes de la famille (principalement la mère; 12/17) de jeunes et de jeunes adultes qui ont subi des méfaits dus à l'usage d'opioïdes et d'autres substances psychoactives, notamment le décès par surdose. Les données des entrevues qualitatives ont fait l'objet d'une analyse thématique réflexive pour en extraire les thèmes. Résultats: L'analyse a fait ressortir les thèmes clés suivants : 1) les obstacles et la stigmatisation présents dans la recherche de soins pour un proche qui consomme des substances psychoactives; 2) le manque de soutien pour répondre aux besoins en santé mentale des membres de la famille. En plus d'avoir de la difficulté à accéder au système et à s'y retrouver, les familles et les proches doivent aussi constamment faire face à de la stigmatisation et de la discrimination de la part du système et des fournisseurs de soins de santé. Un manque de soutien pour les membres de la famille a aussi été signalé, en plus d'un soutien formel très limité pour discuter des questions d'isolement social, de détresse émotionnelle et de deuil lorsqu'un enfant ou un membre de la famille subit des méfaits de la consommation de drogues ou en meurt. Conclusions: Notre étude qualitative apporte des visions approfondies de membres de la famille dont les perspectives ont été marginalisées et exclues de la littérature sur le traitement des problèmes de consommation de substances psychoactives chez les jeunes et les jeunes adultes. Les perspectives des parents, des frères et sœurs et des autres membres de la famille soulignent le besoin d'offrir des services de soutien centrés sur la famille, y compris du soutien en santé mentale pour les aidants. Par conséquent, nous recommandons des stratégies de traitement des dépendances chez les jeunes qui sont davantage «axées sur la famille» pour soutenir non seulement les jeunes qui consomment des substances psychoactives, mais aussi leurs proches.